ICT and its purpose in the pedagogical practice - Diego Enrique Baez Zarabanda (Research in Social Sciences and Technology, 2019)
Information and communications technology (ICT) is currently inserted in the daily activities of a human being and has become a necessary resource, vital for their development up to the point of not conceiving activities without using these. In this sense, the education field is not the exception and has been partially including ICT as support for the teaching practice; however, there is an increasing demand from the students to implement more resources and activities supported by these technologies. A significant distance exists (the known digital divide) between the possibilities offered by different web applications that can support the pedagogical practices and the actual reality of the teaching practice, where the students realize the flaws and the necessity of strengthening the technology skills of the teachers to efficiently develop and orientate such use. In this regard, it is necessary to critically reflect on the possibilities that are offered by different web applications and their impact, their purpose in the pedagogical practice in a way that can serve as a pretext to motivate the teachers in their use and application in the development of their classes, achieving real formative processes. By doing this, students can be offered real, significant learning experiences from the technological, social, and pedagogical view, consolidating in a first instance the abilities of the teachers in the ICT area, as well as the comprehensive learning of their students, being updated on the advances that ICT offers globally, and implementing these permanently in their job as teachers, thus innovating their classes and motivating students towards learning and toward consolidating the use of ICT in the different disciplines, with the human and social component that must characterize us, accomplishing from this standpoint and reflection a pedagogical practice of quality.